XPS and resistive studies on thin films of a copper(II)‐based coordination polymer deposited on functionalized interdigital electrodes. Issue 5 (24th November 2014) - Günthel, Michael; Hübscher, Jörg; Dittrich, Rosemarie; Weber, Edwin; Joseph, Yvonne; Mertens, Florian
ABSTRACT A symmetrical 2‐thiopyrimidine based molecule with an expanded π‐electron system is synthesized and used to form a self‐assembled monolayer (SAM) on gold surfaces. Utilizing chemical vapor deposition a monolayer of (3‐mercaptopropyl)triethoxysilane is formed on silicon dioxide substrates. Both of these SAM coated substrates are characterized by X‐ray photoelectron spectroscopy and the growth of a coordination polymer built up from 5, 5′‐(ethyne‐1, 2‐diyl)bis(2‐hydroxyacetophenone) and copper(II) on dual SAM coated transducers is studied. After the deposition procedure on interdigital electrodes the electrical properties of the polymer are investigated performing resistive measurements. A significant change of the resistance, which depends on the surrounding atmosphere, proves the sensing behavior of the synthesized coordination polymer. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 335–344